Julio Liu, the journeys of a «chinese corner lad» - Tan, Alejandra (2020)
In this paper, we worked with questionnaires and studied historical memories as methodological tools to reconstruct the life story of a Chinese migrant from Guandong (Canton) who was settled in the city of Lima, probably during Leguía’s second term. We described the work experiences that allowed him to visit other cities in northern Peru, and the history of his family in the interior of the Peruvian capital during the second half of the 20th century.